Open-door versus French-door laminoplasty for the treatment of cervical multilevel compressive myelopathy. Issue 3 (March 2015) - Wang, Liang; Wang, Yipeng; Yu, Bin; Li, Zhengyao; Liu, Xiaoyang
Abstract Open-door laminoplasty (ODL) and French-door laminoplasty (FDL) are used to treat cervical multilevel compressive myelopathy. However, differences in outcome between the approaches remain unknown. To investigate treatment differences, we performed a systematic review and meta-analysis. Four comparative trials were identified and analyzed in the review. The results showed that ODL had a higher postoperative Japanese Orthopaedic Association (JOA) score than FDL (weighted mean difference [WMD] = 0.83; 95% confidence interval [CI]: 0.47 to 1.19; p < 0.01). There were no significant differences between the two methods in terms of operative time (WMD = −6.76; 95% CI: −21.70 to 8.18; p = 0.38), intraoperative blood loss (WMD = 41.70; 95% CI: −61.43 to 144.82; p = 0.43), total complication rate (OR = 2.43, 95% CI: 0.22 to 27.04; p = 0.47), postoperative C5 palsy (OR = 1.97, 95% CI: 0.46 to 8.39; p = 0.36), postoperative cervical lordosis (WMD = −0.60; 95% CI: −0.37 to 1.86; p = 0.63) or range of motion (WMD = −4.62; 95% CI: −13.06 to 3.82; p = 0.28). These results suggest that neither cervical laminoplasty approach is superior to the other based on the postoperative radiological data and complication rate, although ODL had higher postoperative JOA score than FDL.